2011
DOI: 10.1186/1471-2334-11-211
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of interventions to increase the uptake of chlamydia screening in primary care: a systematic review

Abstract: BackgroundAs most genital chlamydia infections are asymptomatic, screening is the main way to detect and cases for treatment. We undertook a systematic review of studies assessing the efficacy of interventions for increasing the uptake of chlamydia screening in primary care.MethodsWe reviewed studies which compared chlamydia screening in the presence and the absence of an intervention. The primary endpoints were screening rate or total tests.ResultsWe identified 16 intervention strategies; 11 were randomised c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 29 publications
1
44
0
Order By: Relevance
“…Interventions in pharmacy services reduced suboptimal prescribing [117, 127, 133], and educational interventions improved primary healthcare providers’ identification, assessment, prevention and/or management of obesity in children and adolescents to achieve weight loss [121]. No review focused exclusively on audit and feedback, but multifaceted audit/feedback, reminders, educational outreach visits, and patient-mediated interventions [31, 116, 118, 119] were found to be effective in influencing health professionals’ prescribing practice. Financial incentives combined with educational interventions and audit/feedback have been found to be effective in increasing the practice of generic prescribing [124].…”
Section: Resultsmentioning
confidence: 99%
“…Interventions in pharmacy services reduced suboptimal prescribing [117, 127, 133], and educational interventions improved primary healthcare providers’ identification, assessment, prevention and/or management of obesity in children and adolescents to achieve weight loss [121]. No review focused exclusively on audit and feedback, but multifaceted audit/feedback, reminders, educational outreach visits, and patient-mediated interventions [31, 116, 118, 119] were found to be effective in influencing health professionals’ prescribing practice. Financial incentives combined with educational interventions and audit/feedback have been found to be effective in increasing the practice of generic prescribing [124].…”
Section: Resultsmentioning
confidence: 99%
“…Examples of effective tools include electronic alerts for doctors; syphilis serology included with blood tests performed as part of HIV monitoring, educational workshops for clinic staff; internet-based continuing medical education; free sexual health consultations for patients; biannual STD testing, coupled with brief risk-reduction counseling; and provision of a urine specimen cup at the time of patient registration. [3335] These strategies could be used to increase routine STD screening.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review has shown that a multifaceted workshop approach addressing barriers to screening is more effective than single-component interventions 19. Several studies have demonstrated that the long-term support is pivotal to increase testing by maintaining the importance of chlamydia testing (addressing personal attitudes) and for it to become normal practice (a subjective norm).…”
Section: Discussionmentioning
confidence: 99%